2018
DOI: 10.1007/s00300-018-2293-6
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution in Norwegian lemming Lemmus lemmus in relation to the phase of the cycle

Abstract: Competition between individuals of the same or different species affects spatial distribution of organisms at any given time. Consequently, a species geographical distribution is related to population dynamics through density-dependent processes. Small Arctic rodents are important prey species in many Arctic ecosystems. They commonly show large cyclic fluctuations in abundance offering a potential to investigate how landscape characteristics relates to density-dependent habitat selection. Based on long-term su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…Norwegian Lemming Lemmus lemmus (Linnaeus, 1758) is an iconic population cycling species, the density of which explosively increases every 3-5 years, with subsequent mass movements mystifying people at least since the Middle Ages (Kausrud et al 2008;Lagerholm et al 2017;Le Vaillant et al 2018). The range of Norwegian Lemming covers Norway, eastern Sweden, northern Finland, and the Kola Peninsula in Russia , and this species was thought to be one of a few animals endemic to Fennoscandia (Lagerholm et al 2014(Lagerholm et al , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Norwegian Lemming Lemmus lemmus (Linnaeus, 1758) is an iconic population cycling species, the density of which explosively increases every 3-5 years, with subsequent mass movements mystifying people at least since the Middle Ages (Kausrud et al 2008;Lagerholm et al 2017;Le Vaillant et al 2018). The range of Norwegian Lemming covers Norway, eastern Sweden, northern Finland, and the Kola Peninsula in Russia , and this species was thought to be one of a few animals endemic to Fennoscandia (Lagerholm et al 2014(Lagerholm et al , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…We have applied rel‐NDVI ortho in a number of recent studies where it has been shown to be useful in modelling lemming abundance on a 5–30 m scale (Le Vaillant et al. ) and in modelling species interactions within the terrestrial arctic predator guild (Stoessel et al. ) in mountain tundra ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…We have applied rel-NDVI ortho in a number of recent studies where it has been shown to be useful in modelling lemming abundance on a 5-30 m scale (Le Vaillant et al 2018) and in modelling species interactions within the terrestrial arctic predator guild (Stoessel et al 2018) in mountain tundra ecosystems. But also in biotope mapping in urban and rural landscapes, rel-NDVI ortho has shown to be useful to automatically separate vegetation covered land from non-vegetation, which is a highly desirable separation, even without the attempt to translate rel-NDVI ortho values into an estimation of primary productivity (Akbari et al 2003;Grafius et al 2016;Sk anes and Stoessel 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past three decades, the most important lemming peak was observed in 2011-2012. In these years, lemmings reached peak densities in most of the mountain tundra in Fennoscandia and the entire Kola Peninsula (Emelianova, Abaturov 2017;Ims et al 2017;Le Vaillant et al 2018). The next lemming peak was recorded in 2015 in the Lapland Reserve, however, not in other parts of the peninsula (Kataev 2016;Mammals 2017).…”
Section: Lemming Cyclesmentioning
confidence: 99%